IMPLEMENTASI NILAI-NILAI AKHLAK DALAM PEMBENTUKAN KARAKTER JUJUR SISWA DI MADRASAH TSANAWIYAH NURUL IMAN ULU GEDONG KOTA JAMBI - Terra Aprilya; Jaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to determine that the implementation of moral values can shape the honest character of students at Madrasah Tsanawiyah Nurul Iman Ulu Gedong, Jambi City. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The research results show that: (1) the implementation of moral values in forming students' honest character is carried out thru classroom learning activities, habituation in daily life, and the exemplary behavior of teachers; (2) supporting factors include a religious school environment, the role of teachers as role models, and habituation programs, while inhibiting factors include students' lack of self-awareness, external environmental influences, and the persistence of dishonest behaviors such as cheating; (3) efforts to form an honest character are carried out thru habituation, giving advice and motivation, strengthening religious values, and providing sanctions and rewards. Thus, it can be concluded that the implementation of moral values plays an important role in shaping students' honest character, but it requires support from various parties to function optimally.